Enzymes of Purine Salvage Pathway in Trypanosoma brucei and the Trypanocidal Action of Acyclic Nucleoside Phosphonates - Kotrbová, Zuzana (Jihočeská univerzita, 2014)
This study aims to functionally characterize two enzymes, HGPRT and XPRT, of an essential purine salvage pathway in the infection stage of Trypanosoma brucei. Localization, in vivo function and in vitro activity of these enzymes were characterized. Effect of acyclic nucleoside phosphonates, putative inhibitors of HGXPRT, on the viability of bloodstream form of T. brucei was evaluated.
Enzymes of Purine Salvage Pathway in Trypanosoma brucei and the Trypanocidal Action of Acyclic Nucleoside Phosphonates
Keywords: Trypanosoma brucei; Purine salvage pathway